Random tapping versus just tapping : comparison of effects from mindfulness app - Ngah, Ke En (Nanyang Technological University, 2021)
Mental health is an integral and essential component of health. Although sports participation has its benefits, the nature of competition places a relatively high physiological and psychological demand on athletes. Mindfulness has been touted as a form of intervention to not only improve performance but also psychological well-being. However, there are limited studies that have examined the effects of a random tapping task on a mobile-based application on mindfulness. A total of twenty-two participants were randomly allocated to one of two groups; the control group where they only tapped on one box (n=12) or the experimental group which had to produce a random sequence by tapping on a three by three grid (n=10). It is hypothesized that participants in the experimental group would obtain a higher mindfulness score as compared to the control group. Results of their mindfulness scores were compared using Mann-Whitney U Test. No significant difference was observed between both groups post-intervention (p= 0.6433, effect size= 0.106). The finding suggests the random pattern production was ineffective for improving mindfulness. Future studies may focus on intervarsity athletes who face a myriad of challenges in school and sports.